2015
DOI: 10.5194/angeo-33-1183-2015
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year observations of gravity wave momentum fluxes at low and middle latitudes inferred by all-sky meteor radar

Abstract: • W) were used to estimate the GW momentum fluxes and variances in the MLT region. Our analysis can provide monthly mean altitude profiles of vertical fluxes of horizontal momentum for short-period (less than 2-3 h) GWs. The averages for each month throughout the entire data series have shown different behavior for the momentum fluxes depending on latitude and component. The meridional component has almost the same behavior at the three sites, being positive (northward), for most part of the year. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Interestingly, quasi‐4‐month oscillations with a maximum in July and secondary maxima in February and November in the meridional component are obviously observed at approximately 90 km over Mohe, Mengcheng, and Wuhan. Such an oscillation was also found at low latitudes in the Southern Hemisphere (Andrioli et al, ) as well as in mesospheric winds and temperature inferred from meteor radar and the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER; Das et al, ; Yi et al, ). The possible explanations of this oscillation will be discussed in the Discussion.…”
Section: Observational Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Interestingly, quasi‐4‐month oscillations with a maximum in July and secondary maxima in February and November in the meridional component are obviously observed at approximately 90 km over Mohe, Mengcheng, and Wuhan. Such an oscillation was also found at low latitudes in the Southern Hemisphere (Andrioli et al, ) as well as in mesospheric winds and temperature inferred from meteor radar and the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER; Das et al, ; Yi et al, ). The possible explanations of this oscillation will be discussed in the Discussion.…”
Section: Observational Resultsmentioning
confidence: 70%
“…Hocking (2005) introduced a new approach enabling GW momentum flux calculations in the MLT using meteor radar measurements, which has been distributed worldwide due to its comparatively modest size and cost, as well as its capability to obtain continuous measurements. Recently, this technique has been widely used to study momentum fluxes in high latitude (de Wit et al, 2015;Placke et al, 2015), midlatitude (Andrioli et al, 2015;de Wit et al, 2016;de Wit et al, 2017;Liu et al, 2013;Placke, Stober, & Jacobi, 2011), and tropical regions (Andrioli et al, 2015;Moss et al, 2016). Although the seasonal variations in GW momentum flux have been studied at various sites, their latitudinal variations in the MLT remain rare.…”
Section: Introductionmentioning
confidence: 99%
“…By employing Hocking method, Placke et al (2015) estimated GW momentum fluxes and their annual variation over the Polar region and it is found that interannual variation is consistent during summer months. Andrioli et al (2015) introduced a modified composite day analysis and evaluated latitudinal variation of GW activity using three meteor radars, which exhibited considerable interannual variations. With the help of Monte Carlo analysis, Vincent et al (2010) reported that in order to obtain meaningful results from Hocking method, there should be considerable temporal averaging of the retrieved GW momentum fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Antonita et al, 2008;Clemesha and Batista, 2008;Mitchell, 2009, 2010;Clemesha et al, 2009;Fritts et al, 2010aFritts et al, , b, 2012aVincent et al, 2010;Placke et al, 2011aPlacke et al, , b, 2014Placke et al, , 2015Andrioli et al, 2013aAndrioli et al, , b, 2015Liu et al, 2013;de Wit et al, 2014bde Wit et al, , a, 2016Matsumoto et al, 2016;Riggin et al, 2016). This has largely arisen from a need to obtain improved spatial coverage in the parameterization of GWs and their associated momentum transport in climate models of the whole atmosphere (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fritts et al, 2010bFritts et al, , 2012a have opted to remove the temporal shear imposed by tides and planetary waves by fitting these components to the Cartesian winds, and then subtracting their radial projection from the radial velocities prior to momentum flux estimation. Andrioli et al (2013aAndrioli et al ( , b, 2015 also attempted to remove the same shears by fitting them, directly evaluating the contribution of the fitted components to the momentum fluxes, and then subtracting these from those estimated previously.…”
Section: Introductionmentioning
confidence: 99%